Peran Hak Kekayaan Intelektual terhadap Industri Hijau di Indonesia - Irfandianto, Mohammad; Fahamsyah, Ermanto; Kumala Sari, Nuzulia (WELFARE STATE Jurnal Hukum, 2024)
Legal Protection of Intellectual Property Rights (IPR) has an important role in encouraging innovation and development of environmentally friendly products. Through patents, copyrights, and brand rights, industry players, researchers, and creators are encouraged to create new environmentally friendly solutions. This legal protection aims to encourage innovation and product development by incentivizing rights owners to engage in research and development that benefits society and the environment. This research uses a descriptive method of analysis with a focus on problems which are then analyzed based on reference sources such as laws and regulations, scientific journals, and relevant books. The data collection technique through literature study, in this case, data collection is related to the role of intellectual property rights in the green industry. Intellectual Property Rights have an important role to protect the green industry, with the protection of IPR it will provide efforts to encourage the community to be more innovative in green industry activities and access to technology needed to improve the environment. IPR protection will also greatly affect the development of the national economy and society.